Strengthening Environmental Education in School Curricula - Yarkandi, Asia Hamid (Journal of Education and Vocational Research, 2012)
The concept of ‘the environment’ has changed over time. Early views focused on changing ecosystems and the impact of various forms of pollution. However, the social, economic and cultural dimensions of the environment have been increasingly recognized and the inclusion of sustainable development makes the concept even broader. Environmental education is an approach to acquire the values and clarifying concepts, which aims to develop the necessary skills to understand and appreciate the relationships between human culture and the natural environment vitality, and it is not just the teaching of information and knowledge, but experience in the process of decision making, responsibility, and a law of conduct on issues related to assessment and environmental protection. The importance of environmental education lies when it takes its position between the arts and sciences which are taught, so it turns into a special approach able to take its role in all curricula and in all stages of school and In order to prepare the minds of new generations aware of the concept of environmental education, and work on its application. Therefore, it is through environmental education can make radical changes in ways of thinking and environmental behavior in the society. So that each person is acting like a mature decision maker. This paper highlights the aspects: a) Importance of teaching environmental education in schools b) The approaches adapted to the teaching of environmental education c) Learning strategies of environmental education in school.